Liposomes equipped with cell penetrating peptide BR2 enhances chemotherapeutic effects of cantharidin against hepatocellular carcinoma. (1st January 2017) - Zhang, Xue; Lin, Congcong; Lu, Aiping; Lin, Ge; Chen, Huoji; Liu, Qiang; Yang, Zhijun; Zhang, Hongqi
Abstract: A main hurdle for the success of tumor-specific liposomes is their inability to penetrate tumors efficiently. In this study, we incorporated a cell-penetrating peptide BR2 onto the surface of a liposome loaded with the anticancer drug cantharidin (CTD) to create a system targeting hepatocellular carcinoma (HCC) cells more efficiently and effectively. The in vitro cytotoxicity assay comparing the loaded liposomes' effects on hepatocellular cancer HepG2 and the control Miha cells showed that CTD-loaded liposomes had a stronger anticancer effect after BR2 modification. The cellular uptake results of HepG2 and Miha cells further confirmed the superior ability of BR2-modified liposomes to penetrate cancer cells. The colocalization study revealed that BR2-modified liposomes could enter tumor cells and subsequently release drugs. A higher efficiency of delivery by BR2 liposomes as compared to unmodified liposomes was evident by evaluation of the HepG2 tumor spheroids penetration and inhibition. The biodistribution studies and anticancer efficacy results in vivo showed the significant accumulation of BR2-modified liposomes into tumor sites and an enhanced tumor inhibition. In conclusion, BR2-modified liposomes improve the anticancer potency of drugs for HCC.